Status and trend of ecosystem services of Madhupur Sal forest in Bangladesh - Saha, Soumitra; Hasan, Shaikh Shamim; Haque, Md. Enamul; Ahamed, Tofayel; Hasan, Shahriar (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Madhupur Sal forest comprises a substantial portion of Bangladesh's Sal Forest area, but deforestation is negatively affecting its overall environment in recent times. This study examines the present status and changing trend of ecosystem services over the years in Madhupur Sal forest. Data were collected from 120 respondents with two focus group discussions through in-person interviews. The major portion of the respondents comprised Garo ethnic people of the area. According to the findings, the respondents identified 20 different ecosystem services where soil erosion prevention, mental peace, and soil fertility maintenance were perceived as top services. Regulating and cultural services existed as the most prominent services of the study area. The forest experienced a massive trend of changes over the last ten years. Most of the respondents (64.80%) observed an increase in the agricultural land area during the period. As reported by most of them (74.50%), the marketplace of the local handicraft industry was getting narrower at a rapid rate while the agricultural land area was increasing at a slower rate (68.60%). All of the services, from provisioning to regulating, exhibited a declining trend, and an extreme trend was observed in case of supporting services, as stated by 95.05% of the respondents. The research findings offer useful baseline information on the ecosystem service research for Bangladesh.